The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1142/s0219635216500084
|View full text |Cite
|
Sign up to set email alerts
|

Using fMRI to compare the effects of benzylpiperazine with dexamphetamine — Their differences during the Stroop paradigm

Abstract: Despite BZP and DEX reportedly inducing similar subjective effects, there are different patterns of neural activation. We believe this differential activity is due to pharmacological differences in their receptor binding profiles and that subsequent inhibitory effects might be due to their direct effect on dopaminergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In HC individuals, greater D2R-related binding was associated with shorter interference delays, consistent with the hypotheses. While research into the influence of dopaminergic agents on Stroop performance in healthy populations are mixed [55][56][57], greater availability of striatal D2R has been associated with improved cognitive performance more broadly [58]. In the current study, this association between D2R binding and cognitive performance was not present in CUD participants.…”
Section: D2r/d3r and Dmn Suppression During Cognitive Controlmentioning
confidence: 49%
“…In HC individuals, greater D2R-related binding was associated with shorter interference delays, consistent with the hypotheses. While research into the influence of dopaminergic agents on Stroop performance in healthy populations are mixed [55][56][57], greater availability of striatal D2R has been associated with improved cognitive performance more broadly [58]. In the current study, this association between D2R binding and cognitive performance was not present in CUD participants.…”
Section: D2r/d3r and Dmn Suppression During Cognitive Controlmentioning
confidence: 49%
“…The study found that BZP caused an increase in activity in the inferior frontal gyrus (IFG) and a decrease in the anterior cingulate cortex. In contrast, dexamphetamine reduced activity in IFG activity and increases it in thalamus (Curley et al 2016). We have also shown that a single oral dose of either BZP or TFMPP, but not the combination of BZP/TFMPP, affected the auditory sensory-evoked P300 potential in a manner similar to dexamphetamine .…”
Section: Introductionmentioning
confidence: 53%